The recovery from agro-industrial wastes provides different profiles of anti-inflammatory polyphenols for tailored applications - Abbasi-Parizad, Parisa; Scarafoni, Alessio; Pilu, Roberto; Scaglia, Barbara; De Nisi, Patrizia; Adani, Fabrizio (Frontiers in Sustainable Food Systems, 2022)
Food and agro-industrial processing produce a great amount of side-stream and waste materials that are excellent sources of functional bioactive molecules such as phenolic compounds that recover them can be beneficial not only for food sustainability but also to human for many industrial applications such as flavor compounds and therapeutic applications such as antimicrobial and anti-inflammatory. The treatments and extraction techniques have major effects on the recovery of bioactive compounds. Along with the conventional extraction methods, numerous innovative techniques have been evolved and have been optimized to facilitate bioactive extraction more efficiently and sustainably. In this work, we have summarized the state-of-the-art technological approaches concerning novel extraction methods applied for five most produced crops in Italy; Grape Pomace (GP), Tomato Pomace (TP), Olive Pomace (OP), Citrus Pomace (CP), and Spent Coffee Grounds (SCG), presenting the extraction yield and the main class of phenolic classes, with the focus on their biological activity as an anti-inflammatory in vitro and in vivo studies via describing their molecular mechanism of action.